2013
DOI: 10.1086/670224
|View full text |Cite
|
Sign up to set email alerts
|

Copper Continuously Limits the Concentration of Bacteria Resident on Bed Rails within the Intensive Care Unit

Abstract: Cleaning is an effective way to lower the bacterial burden (BB) on surfaces and minimize the infection risk to patients. However, BB can quickly return. Copper, when used to surface hospital bed rails, was found to consistently limit surface BB before and after cleaning through its continuous antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 12 publications
6
67
0
1
Order By: Relevance
“…Recent clinical trials showed that covering hightouch surfaces in hospital rooms with copper can significantly decrease the bacterial burden and can reduce the number of hospital-acquired infections by more than 50% (35,(45)(46)(47)(48). Because A. baumannii fomite-associated hospital outbreaks have been documented, specifically from a contaminated hospital bed and burn theater, evidence that copper effectively eliminates environmental A. baumannii is important (49).…”
Section: Figmentioning
confidence: 99%
“…Recent clinical trials showed that covering hightouch surfaces in hospital rooms with copper can significantly decrease the bacterial burden and can reduce the number of hospital-acquired infections by more than 50% (35,(45)(46)(47)(48). Because A. baumannii fomite-associated hospital outbreaks have been documented, specifically from a contaminated hospital bed and burn theater, evidence that copper effectively eliminates environmental A. baumannii is important (49).…”
Section: Figmentioning
confidence: 99%
“…Their antimicrobial properties are now well established, and copper has been recently registered at the U.S. Environmental Protection Agency as the first solid antimicrobial material . Several studies have been conducted to evaluate the antimicrobial efficacy of surfaces composed of Cu or Cu alloys, both in vitro and in the clinical setting Schmidt et al 2013). Issues regarding the variation in the constituents of Cu alloys and the stability of Cu-impregnated surfaces have, however, raised concerns about the practicality of using Cu as selfsanitation material on flexible surfaces (Torres et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 They also have been shown to continuously reduce the concentration of total bacteria on bed rails within intensive care unit (ICU) rooms. 8 The present study was designed to assess the effectiveness of ABS-G2015 (Allied BioScience, Point Roberts, WA), a formulation of a quaternary ammonium organosilane compound that binds to surfaces and produces a residual (ie, long-term) disinfecting activity. Our initial laboratory work demonstrated ABS-G2015's effectiveness against a wide range of pathogenic bacteria (eg, MRSA, Pseudomonas aeruginosa) and viruses (eg, MS-2 virus).…”
mentioning
confidence: 99%